2018
DOI: 10.1177/0886260518818431
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Foreclosures and Intimate Partner Violence During the U.S. Housing Crisis

Abstract: The recent U.S. housing crisis led to increases in neighborhood foreclosures and stress. Intimate partner violence (IPV) is linked to neighborhood stress, but less is known about whether foreclosures aggravate neighborhood conditions affecting IPV. Using police, foreclosure, and census data for three cities in the Phoenix region coupled with cross-sectional time series modeling, we find a direct effect of foreclosures on IPV, with the largest effects appearing at the end of the housing crisis. Our findings sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Foreclosures, both at an individual and neighborhood level, are important stressors related to child maltreatment (Bartholet et al, 2011; Freisthler, 2004; Sedlak et al, 2010). Indeed, neighborhood foreclosures have been linked to increases in interpersonal violence (IPV; Wallace et al, 2018), while larger macro-level trends in foreclosures are associated with an increase in incidences of child maltreatment (Frioux et al, 2014; Huang et al, 2011; Lindo et al, 2013; Wood et al, 2012). In our study, we examined the impact of foreclosures on child maltreatment in neighborhoods in the city of Cleveland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreclosures, both at an individual and neighborhood level, are important stressors related to child maltreatment (Bartholet et al, 2011; Freisthler, 2004; Sedlak et al, 2010). Indeed, neighborhood foreclosures have been linked to increases in interpersonal violence (IPV; Wallace et al, 2018), while larger macro-level trends in foreclosures are associated with an increase in incidences of child maltreatment (Frioux et al, 2014; Huang et al, 2011; Lindo et al, 2013; Wood et al, 2012). In our study, we examined the impact of foreclosures on child maltreatment in neighborhoods in the city of Cleveland.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, unemployment might trigger foreclosure, while residential instability is a natural byproduct of a home being repossessed by the bank. Neighborhood factors have been shown to influence rates of child maltreatment (Coulton et al, 1995; Garcia & Herrero, 2006; Korbin et al, 2000; Wang & Maguire-Jack, 2018), as well as other forms of more “private” violence, such as spousal or intimate partner violence (Boggess & Chamberlain, 2020; Wallace et al, 2018). Future research should attempt to tease apart the interrelationship between these processes to gain a better understanding of how neighborhood structure, foreclosure, and child maltreatment might be related.…”
Section: Discussionmentioning
confidence: 99%
“…Low-income families face particular challenges and disadvantages during the critical period around pregnancy, birth, transition to parenthood, and early childhood. These include relatively worse access to and quality of health care [29,30] and increased exposure to environmental, neighborhood, or housing-related risks [8,[31][32][33][34]. The health risks associated with pregnancy, childbirth, and the postpartum period are significant, particularly for low-income households.…”
Section: Protocol Paper Focus: Maternal and Child Health Outcomes Durmentioning
confidence: 99%
“…We also include a measure of the percent female-headed households with children because prior research has found this to be a consistent and strong predictor of violence (Lauritsen & Schaum, 2004;Lauritsen & White, 2001;Pinchevsky & Wright, 2012). Finally, because our panel data cover the years of the housing market crash in the mid-2000s, we include a binary variable indicating the crash years (2006-2008) (Wallace et al, 2018).…”
Section: Neighborhood Characteristicsmentioning
confidence: 99%
“…Certain neighborhood factors such as residential instability and poverty weaken residents' social ties and the informal social control that regulates crime and victimization. An increasing body of research has also connected neighborhood context to intimate partner violence (IPV) specifically, finding that factors such as disadvantage (Benson et al, 2003(Benson et al, , 2004Van Wyk et al, 2003), resource deprivation, (Miles-Doan, 1998), and foreclosures (Wallace et al, 2018) are linked to increased IPV. Current neighborhoodlevel IPV research, however, has largely focused on aggravating factors associated with higher rates of IPV; less attention has been focused on mitigating factors that may ameliorate the influence of structure on victimization.…”
Section: Introductionmentioning
confidence: 99%